Bulbilhos aéreos de alho, provenientes de escapes florais, são infectados por vírus - Mituti, Tatiana [UNESP]; Oliveira, Milena Leite [UNESP]; Nardini, João Paulo Calore [UNESP]; Moura, Monika Fecury [UNESP]; Hoffmann, Maria Isabel Motta [UNESP]; Guimarães, Leysimar Ribeiro Pitzr [UNESP]; Sakate, Renate Krause [UNESP]; Pavan, Marcelo Agenor [UNESP] (Grupo Paulista de Fitopatologia, 2014)
In commercial garlic fields, plants naturally infected by viruses of the genera Allexivirus, Carlavirus and Potyvirus are commonly observed. Aerial bulbils may be an alternative for the propagation of virus-free garlic plants. Thus, the aim of this study was to analyze the rate of virus perpetuation from infected plants to aerial bulbils. Aerial bulbils obtained from infected plants were analyzed by RT-PCR using universal primers for the genera Allexivirus, Carlavirus and Potyvirus. Results showed that the perpetuation of different viruses from the bulb to aerial bulbils is high, impairing the direct use of aerial bulbils from virus-infected matrix plants. This methodology should use solely virus-free plants.

Em campos de produção comercial de alho é comum observar plantas naturalmente infectadas por vírus dos gêneros Allexivirus, Carlavirus e Potyvirus. Os bulbilhos aéreos podem ser uma alternativa para a propagação de plantas de alho livres de vírus. Desta forma, o objetivo deste trabalho foi analisar a taxa de perpetuação dos vírus de plantas infectadas para os bulbilhos aéreos. Os bulbilhos aéreos obtidos de plantas infectadas foram analisados por RT-PCR utilizando oligonucleotídeos universais para os gêneros Allexivirus, Carlavirus e Potyvirus. A taxa de perpetuação foi de 65% para allexivírus, 20% para carlavírus e 82,22% para potyvírus. Os resultados demonstraram que a perpetuação dos diferentes vírus do bulbo para os bulbilhos aéreos é elevada, inviabilizando a utilização direta dos bulbilhos aéreos provenientes de plantas matrizes infectadas por vírus. Esta metodologia deve ser utilizada somente a partir de plantas isentas de vírus.
Garlic aerial bulbils, from floral scapes, are infected by viruses
Keywords: allexivírus; carlavírus; potyvírus; propagação; allexivirus; carlavirus; potyvirus; propagation